A Study to Evaluate the Effectiveness of Planned Teaching Program on Knowledge Regrading Menstrual Disorders Among Girls in Selected PU Colleges at Vijayapur - Navalkar, Alka (International Journal of Nursing Research, 2024)
Aim: The aim of study was to evaluate the effectiveness of planned teaching program (PTP) on knowledge regrading menstrual disorders among girls in selected PU colleges at Vijayapur. Materials and Methods: Pre-experimental (one group pre-test and post-test) research design was employed in this study. The PTP is the independent variable, while the knowledge of the adolescent girls enrolled in PU College regarding menstrual diseases is the dependent variable. The location of the teenage ladies at particular PU College in Vijayapur. To choose the subjects, a simple random sampling procedure is utilized. The sample consists of 60 teenage girls who attend PU College in Vijayapur. Structured knowledge questionnaires were employed as the study’s instrument to gauge adolescent girls’ knowledge about menstrual problems. Results: This study aims to evaluate the efficacy of a PTP in terms of its impact on knowledge acquisition as measured by post-test scores. Based on the pre-test and post-test results, it is evident that the adolescent girls’ knowledge regarding menstrual disorders significantly increased from a mean score of 14–25.2. This indicates that the PTP effectively enhances the knowledge of adolescent girls in relation to menstrual disorders. Conclusion: The findings of study indicate that the initial level of knowledge among adolescent girls regarding menstrual disorders was measured at 14, while their knowledge after the teaching program increased to 25.2. This significant difference strongly suggests that the implemented educational intervention effectively enhances the awareness of menstrual disorders among adolescent girls.